Anaesthetic Management of Ischemic Heart Disease Patients in Noncardiac Surgery - Munir, Md Mahbubul Hasan; Rahman, Md Mushfiqur; Shaheen, Shafiul Alam (Ibrahim Cardiac Medical Journal, 2016)
Perioperative myocardial infarction is one of the most important predictors of short and long term morbidity and mortality associated with noncardiac surgery. Myocardial infraction occurs whenever myocardial oxygen supply does not match myocardial oxygen demand. Intraoperative ischemia can be precipitated by increase in myocardial oxygen demand caused by tachycardia, hypertension, anaemia, stress, sympathomimatic drugs or discontinuation of beta blocker. Clinical predictors of perioperative cardiac morbidity are acute myocardial infraction or recent myocardial infraction, unstable or severe angina, decompensated heart failure, severe valvular disease, mild angina pectoris, previous myocardial infraction, diabetic mellitus etc. The preoperative history is meant to elicit the severity, progression and functional limitations imposed by ischemic heart disease. Limited exercise tolerance in the absence of significant lung disease is very good evidence of decreased cardiac reserve. The basic challenges during induction and maintenance of anaesthesia in patients with ischemic heart disease are prevent myocardial infraction by increasing myocardial O2 supply and reducing myocardial O2 demand and monitor for ischemia and to treat ischemia if it develops. There are no one best myocardial protective agents or technique. Maintenance of balance between myocardial oxygen supply and demand is more important than the specific technique or drugs selected to produce anaesthesia and muscle relaxation. Potential benefits of a regional anaesthetic include excellent pain control, a decreased incidence of deep vein thrombosis (DVT) in some patients and the opportunity to continue the block into the postoperative period. The postoperative period appears to present the highest risk for cardiac morbidity. It is during this period where 67% of the ischemic events occur. Effective pain management is essential to prevent these adverse outcomes. Successful perioperative evaluation and treatment of cardiac patients undergoing noncardiac surgery requires careful teamwork and communication between patient, anaesthesiologist and surgeon. Ibrahim Cardiac Med J 2014; 4(2): 56-60